2015
DOI: 10.1088/0031-9155/60/7/2751
|View full text |Cite
|
Sign up to set email alerts
|

Development of 4D mathematical observer models for the task-based evaluation of gated myocardial perfusion SPECT

Abstract: This paper presents two 4D mathematical observer models for the detection of motion defects in 4D gated medical images. Their performance was compared with results from human observers in detecting a regional motion abnormality in simulated 4D gated myocardial perfusion (MP) SPECT images. The first 4D mathematical observer model extends the conventional channelized Hotelling observer (CHO) based on a set of 2D spatial channels and the second is a proposed model that uses a set of 4D space-time channels. Simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In order to objectively optimize the weighting parameters, task-based evaluation and optimization are needed. In Lee et al (2015aLee et al ( , 2015b, human observer studies with ROC analysis and a channelized hotelling observer (CHO) with 4D channels were used to optimize the parameters of a Gibbs prior for the 4D MAP reconstruction for the task of detecting regional wall motion abnormality. Both mathematical and human observers showed that with optimal weighting parameters, the 4D MAP reconstruction is superior to 3D reconstruction for detecting abnormal wall motions.…”
Section: Optimization and Evaluation Of Multi-dimensional Image Recon...mentioning
confidence: 99%
“…In order to objectively optimize the weighting parameters, task-based evaluation and optimization are needed. In Lee et al (2015aLee et al ( , 2015b, human observer studies with ROC analysis and a channelized hotelling observer (CHO) with 4D channels were used to optimize the parameters of a Gibbs prior for the 4D MAP reconstruction for the task of detecting regional wall motion abnormality. Both mathematical and human observers showed that with optimal weighting parameters, the 4D MAP reconstruction is superior to 3D reconstruction for detecting abnormal wall motions.…”
Section: Optimization and Evaluation Of Multi-dimensional Image Recon...mentioning
confidence: 99%
“…Currently, there are limited studies of spatiotemporal numerical observers. Previously, Lee et al, 38,39 developed a numerical 4D CHO and applied it to the task-based evaluation of gated-myocardial perfusion SPECT images. They reorganized the 4D images into a set of 2D cine images, treating a 4D image as a set of moving 2D images.…”
Section: Introductionmentioning
confidence: 99%